2011
DOI: 10.1186/bcr3072
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocytes predict response to anthracycline-based chemotherapy in estrogen receptor-negative breast cancer

Abstract: IntroductionInfiltration of breast tumors by tumor-infiltrating lymphocytes (TIL) has been associated with sensitivity to anthracycline-based chemotherapy. However, it is unclear whether this is true within the estrogen receptor-alpha (ER)-negative subset of breast tumors that frequently manifest high TIL levels.MethodsThe association of TIL with short-term and long-term clinical response to anthracycline-based therapy was assessed in two independent ER-negative breast cancer cohorts in which patients were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
233
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(257 citation statements)
references
References 48 publications
16
233
3
5
Order By: Relevance
“…The results of the present study revealed that the intratumoral expression of CD8 + TIL may be predictive of pCR in this patient population. Similar to previous studies (17,21,22,(40)(41)(42), 56% of patients with high intratumoral expression of CD8 + TIL achieved a pCR, in contrast with 13.3% for patients with low intratumoral CD8 + TIL. Denkert et al (17) investigated intratumoral and stromal lymphocytes in a total of 1,058 pre-therapeutic BC core biopsies from two neoadjuvant anthracycline/taxane-based studies.…”
Section: Discussionsupporting
confidence: 67%
“…The results of the present study revealed that the intratumoral expression of CD8 + TIL may be predictive of pCR in this patient population. Similar to previous studies (17,21,22,(40)(41)(42), 56% of patients with high intratumoral expression of CD8 + TIL achieved a pCR, in contrast with 13.3% for patients with low intratumoral CD8 + TIL. Denkert et al (17) investigated intratumoral and stromal lymphocytes in a total of 1,058 pre-therapeutic BC core biopsies from two neoadjuvant anthracycline/taxane-based studies.…”
Section: Discussionsupporting
confidence: 67%
“…High-intratumoral levels of CD8 C T cells 43 or TILs 36,44 are associated with better clinical responses to anthracycline-based chemotherapy. West et al 45 reported that highlevels of lymphocyte GE were associated with a high rate (74%) of complete pathological responses to neoadjuvant anthracyclinebased chemotherapy. In 2011, Sabatier et al 20 showed, by geneexpression profiling, that "Immune High" patients (59%) were more likely to present pCR than "Immune Low" patients (43%), but this difference was not significant (p D 0.29).…”
Section: Discussionmentioning
confidence: 99%
“…TIL has been confirmed to be highly present in TNBC and related to increased pCR rate and improved disease-free survival (DFS) and OS after chemotherapy. [58][59][60] In neoadjuvant GeparSixto and PrECOG0105 trials, TIL levels are positively associated with pCR rate among TNBC patients. LPBC is defined as breast cancer with lymphocytes in 50% or more of tumor or stroma, which was also proved to be associated with pathologic response in GeparSixto trial.…”
Section: Emerging Biomarkersmentioning
confidence: 99%